Characterisation of PVD-TiN coated austempered ductile iron: Effects of nodule count and austempering temperature - Colombo, Diego Alejandro (2011)
In this work PVD-TiN coatings are deposited on ADI substrates austempered at 280 and 360°C, with nodule counts varying between 490 and 1 100 nod/mm2. The deposition is performed at 300°C by the arc ion plating technique. The effects of the substrates' microstructure on the characteristics of the coatings and the possible changes in ausferritic microstructure owing to the effects of the deposition process are evaluated. The existing phases, preferred orientation, film thickness, hardness, Young's modulus, surface topography and adhesion of each coated sample are determined. A metallographic characterisation of the ausferritic matrices and determination of the retained austenite content are performed before and after deposition. The results obtained indicate that PVD-TiN coatings feature a preferred orientation of (111) planes parallel to the surface and film thicknesses of about 2m m. Knoop hardness is influenced by the substrates characteristics, the values range from 1 700 to 2 100 HK0.015. Nanohardness values are close to 25 GPa, while Young's modulus shows some scattering (323 to 336 GPa). The surface topography is dependent on the microstructure of the substrates and the surface preparation method employed as well as on the deposition process used. The adhesion strength quality of the coatings, according to the Rockwell-C adhesion test, can be related to HF1-HF2 and is affected neither by the hardness differences between the different substrates nor by the nodule count variation. After the coating process, the microstructure of ADI substrates only suffers negligible changes and the amount of retained austenite decreases slightly.